EKSPLORASI ETNOMATEMATIKA ARITMATIKA SOSIAL PADA TAPAI SINGKONG SEBAGAI SUMBER PEMBELAJARAN MATEMATIKA - Alifia Nadhira; Ammamiarihta Ammamiarihta (LPPM Universitas Bina Bangsa, 2024)
This research aims to overcome a problem in the field of mathematics by utilizing the concept of ethnomathematics, especially in terms of social arithmetic. Apart from that, this research can also be used as a mathematics learning resource that introduces Indonesian culture through the use of traditional food. This research is a type of qualitative descriptive research that uses an ethnographic approach as a research method. This research will use various methods such as interviews, observation, documentation and literature review to collect data. The researchers also collected secondary data, namely taking quotations from several journals as references. In data analysis, it can be concluded that of the two groups of cassava tapai traders studied, the first group experienced an increase in profits of 39.86% every day. If all the goods are sold, the second group will get a profit of 182.68% every day. So it can be concluded that the second group of cassava tapai traders received greater benefits than the first group of cassava tapai traders